Stratification of bilingualism in Kyrgyzstan in the context of leading languages - Zakirov, Alymjan; Turgunova, Gulmira A.; Ibraimova, Gulsaira O.; Shabdanaliev, Nurbek A. (Linguistics and Culture Review, 2021)
The article is devoted to sociolinguistic monitoring of Bilingualism in the Regions of Kyrgyzstan. It is commonly known that Kyrgyzstan is a polyglossic state with many languages and many nationalities. Bilingualism is reflecting on language situation in regions, which makes the article extremely relevant. The purpose of this paper is to provide an overview of the current situation in Kyrgyzstan, affected by the previous experiences of multilingualism, examples of the neighboring countries, and new nation-building expectations. The focus of our discussion is the changing role of Russian and its use as the language at the service of the growing Asian economies, denationalized and free from the Soviet historical-cultural background. The new hybrid culture and partly regionalized Russian language serve to unify Central Asian republics with Russia. The leading method for the study was the study of the Kyrgyz language in the context of the history the Kyrgyz people and the geographical position of the Republic of Kyrgyzstan. It was found out that ? number of diverse and complex conditions and factors lead to life-long bilingualism. There are no theories of language studying and training is proficient of explaining bilingual spoken behavior and the mechanisms leading to bilingual language growth.